2000
DOI: 10.1161/01.str.31.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Increased Matrix Metalloproteinase-9 Activity in Unstable Carotid Plaques

Abstract: Background and Purpose-Acute disruption of atherosclerotic plaques precedes the onset of clinical syndromes, and studies have implicated a role for matrix metalloproteinases (MMPs) in this process. The aim of this study was to establish the character, level, and expression of MMPs in carotid plaques and to correlate this with clinical status, cerebral embolization, and histology. Methods-Plaques were obtained from 75 consecutive patients undergoing carotid endarterectomy and divided into 4 groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
235
2
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(276 citation statements)
references
References 41 publications
16
235
2
12
Order By: Relevance
“…Indeed, MMP-9 was highly expressed in the shoulder regions of advanced atherosclerotic lesions (Galis et al, 1994;Brown et al, 1995). Its concentration and activity were significantly higher in unstable atheroseclerotic plaque with intense inflammatory cell infiltration, hence contributing to the plaque rupture ultimately (Loftus et al, 2000;Pasterkamp et al, 2000). Some cross-sectional studies have reported that the plasma MMP-9 level was significantly higher in CAD patients, in particular in acute MI, than in control subjects (Kai et al, 1998;Tayebjee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MMP-9 was highly expressed in the shoulder regions of advanced atherosclerotic lesions (Galis et al, 1994;Brown et al, 1995). Its concentration and activity were significantly higher in unstable atheroseclerotic plaque with intense inflammatory cell infiltration, hence contributing to the plaque rupture ultimately (Loftus et al, 2000;Pasterkamp et al, 2000). Some cross-sectional studies have reported that the plasma MMP-9 level was significantly higher in CAD patients, in particular in acute MI, than in control subjects (Kai et al, 1998;Tayebjee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the full functional repertoire of NGAL remains to be elucidated. Of particular interest is the finding that NGAL inhibits MMP-9 inactivation, leading to enhanced proteolytic activity with prolonged effects on collagen degradation (27). Indeed, Hemdal et al have found increased expression and co-localization of MMP-9 and NGAL in atherosclerotic lesions, especially in myocardial infarction (15).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 seems to play an important role in this process in obese individuals, as evident by its elevated plasma concentrations in these subjects [5,10,11]. In addition, clinical studies have shown that alteration in the expression or activity of MMPs and/or TIMPs is an important mechanism underlying the pathophysiology of some cardiovascular diseases [5][6][7][8] and contributes to ventricular dysfunction [6] and atherosclerotic lesions [9]. Studies evaluating circulating levels of MMP-8 (neutrophil collagenase) in obese women without associated comorbidities have not yet been evaluated, although some studies have shown higher MMP-8 levels in subjects presenting with cardiovascular disorders [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%